Analysis of the Economic Benefits of Minapadi Farming in Rain-Fed Swamp Land on Farmer Household Income in Epeesi Village Basala District South Konawe Regency - Samsul Alam Fyka; Idrus Salam; La Arwahi (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2023)
Minapadi is a system that combines rice and fish crops in one land. This system will certainly provide several benefits for farmers. The purpose of this study was to determine the economic contribution of the rice farming system's application to farmers' household income. The number of respondents is all lowland rice farmers who apply the Minapadi farming, namely 68 people. The method of determining the sample is determined by the census method. The data used are primary data sourced from interviews with respondents and secondary data from related agencies. The data analysis used is income analysis and contribution analysis. The results The economic benefits of implementing Minapadi farming on rainfed swampy land include providing additional income to farmer households amounting to Rp2,369,616 per hectare per month, with a contribution of 83%. This is due to the revenue generated from selling paddy rice, fish sales, and rental income from freshwater fishing tourism.